Anatomy of the Uncinate Process in Avian: A Literature Review - Dhamayanti, Yeni; Suryadiningrat, Muhammad; Alvaro, Aloisius Primo; Sinaga, Melina Martupauli; Çalışkan, Hakan; Firdausy, Lintang Winantya (Universitas Airlangga, 2025)
The uncinate process (UP), a dorsocaudal projection from the vertebral ribs, represents a pivotal adaptation in the avian thoracic skeleton, serving as a mechanical brace that enhances respiration and stabilizes the trunk during flight. This literature review synthesizes anatomical, functional, developmental, and evolutionary perspectives on UP morphology across diverse bird taxa. A systematic search spanning 2015–2025 identified 20 relevant studies detailing the structural variability of UPs—categorized as short, intermediate, or long—correlating with flight styles, such as soaring, diving, or terrestrial locomotion. Long UPs, observed in species like penguins and cormorants, are associated with enhanced ventilatory efficiency and thoracic rigidity for high-energy propulsion, while short UPs in flightless birds reflect reduced respiratory demand. Developmental studies reveal ontogenetic shifts from cartilaginous to ossified UPs, aligned with increasing locomotor activity. Evolutionary analysis underscores the UP as a conserved synapomorphy of Aves, with convergent elongation in unrelated taxa emphasizing its functional significance. Structural integration with intercostal musculature and adjacent ribs enables efficient force transmission and thoracic stabilization, vital for maintaining trunk posture during flight. Beyond its evolutionary relevance, UP morphology has practical implications in avian health, surgical ventilation strategies, and bioinspired biomechanical applications. This review highlights the UP as an underappreciated yet essential component of avian musculoskeletal architecture, offering insights into respiratory evolution, ecological adaptation, and comparative vertebrate anatomy. Future investigations should expand morphometric databases and apply high-resolution imaging and biomechanical modeling to further elucidate the functional roles of the UP in avian physiology and evolution.